Simultaneous SAXS and WAXS Study on the Guest Exchange Process of Syndiotactic Polystyrene: Crystalline Complex Formation with Triethylene Glycol Dimethyl Ether. Issue 17 (15th May 2013) - Kaneko, Fumitoshi; Seto, Naoki; Sasaki, Keita; Sakurai, Shinichi; Kimura, Tsuyoshi; Milano, Giuseppe; Venditto, Vincenzo; Oliva, Leone
Abstract Syndiotactic polystyrene (sPS) forms cocrystals with a variety of chemical compounds. The guest molecules can be easily replaced with other kinds of molecules under certain conditions. The guest‐exchange process, on exposure to liquid triethylene glycol dimethyl ether (TEGDME), is followed by time‐resolved simultaneous small‐angle and wide‐angle X‐ray scattering to clarify the structure changes in molecular‐level and higher‐order structures. It is clarified that the exchange from the original guest chloroform to the new guest TEGDME takes place mainly after a certain incubation time, in parallel with the expansion of the lamellar period. The occurrence of the ϵ cocrystal during this process and the influence of the amount of chloroform on the incubation time are also studied.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>